Students’ Perception on the Use of Twitter as a Learning Media for English Vocabulary and Reading at the Fifth Semester of English Education Department at University - Utami Nur Karimah; Raihan Athaya Ramadhan Tarigan; Julaika Aristianty; Adhwa Alfi Najmah; Siti Nurul Azkiyah (Institut Agama Islam Negeri Palopo, 2024)
As digital technology continues to reshape educational methods, understanding students' perceptions regarding Twitter's effectiveness as a learning tool for enhancing English vocabulary and reading comprehension is essential for educators and researchers seeking to optimize language learning strategies. Despite a large amount of literature on social media platforms, there has been limited exploration of the specific features of Twitter that facilitate interactive learning, group interaction, vocabulary and reading development, especially when compared to other social media platforms. The purpose of this study was to investigate the perceptions and opinions of fifth-semester students regarding the use of Twitter as a new alternative media for improving students' English vocabulary and reading skills. This research used a qualitative approach, with data collected through interviews and presented by thematic analysis. There are 10 students from the 5th semester in the English Education Department UIN Jakarta were selected as the participants through purposive sampling. According to the interview, there are 8 students who agree and they mentioned that Twitter features like the direct message, English posts, and comment sections are useful for improving their English vocabulary and reading. The study's findings demonstrate how beneficial it is for students to use Twitter as a learning media to increase their vocabulary and reading comprehension in English.